Social development in childhood and adolescence a contemporary reader - Killen, Melanie; Coplan, Robert J. 1967- (Wiley-Blackwell, 2011)
"The field of social development examines some of the most fascinating topics of current research in psychology: the social nature of humans, the origins of morality, the nature of prejudice in childhood, bullying and victimization, the role of emotions in development and communication, and characteristics of healthy and unhealthy peer and parent-child relationships. This book brings together the most significant classic and contemporary writings in this area to provide a comprehensive overview of the field in a format that is both engaging for students and intuitive for instructors. Integrating the most important articles with tools to help students understand the material, Social Development in Childhood and Adolescence provides a full introduction to the theory and research currently underway in this dynamic field."--Provided by publisher.